(untitled) (World Science, 2024)
Cardiovascular diseases (CVD) are the leading cause of death and disability among adults in the world. The key position in the structure of causes of death from CVD is occupied by coronary heart disease (CHD), the most common form of which is stable angina. The goals of treatment for patients with chronic angina should be to relieve symptoms and reduce mortality. This will allow patients to feel better and live longer. The traditional hemodynamic approach to the treatment of CAD is based on the belief that increasing oxygen supply and decreasing cardiomyocyte oxygen demand improves symptoms. However, clinical trial data demonstrate that about a third of patients, despite antianginal therapy, continue to experience anginal pain. Traditional tactics for managing patients with stable angina usually involve the use of drugs that affect circulatory parameters (heart rate, blood pressure). The article presents a clinical case demonstrating the effectiveness of trimetazidine monotherapy in stable coronary artery disease, when the use of first-line drugs (beta blockers, calcium antagonists and nitrates) is not possible. Trimetazidine modulates cardiac metabolism without changing hemodynamic functions, so its use in this clinical situation is optimal. Modulators of cardiac metabolism open the way to a deeper understanding of CAD and its general clinical manifestations as an energy disorder, not just an imbalance between the demand and supply of oxygen and metabolites